The The Influence of Organizational Justice and Organizational Support on Work Motivation Through Work Engagement as a Mediating Variable - Doni Febrian Ashadimas; Nugraha Saefudin (International Journal of Business, Management and Economics, 2026)
Work motivation is an essential factor in supporting employee performance and the effectiveness of higher education institutions. However, employee motivation may decline when organizational justice, organizational support, and psychological attachment to work are not optimally managed. This study aims to analyze the effect of organizational justice and organizational support on work motivation, with work engagement as a mediating variable. This research employed a quantitative approach with descriptive and verification methods. The population consisted of 1,158 educational staff at the Indonesian University of Education, while the sample comprised 298 respondents determined using the Slovin formula with a 5% margin of error and selected through simple random sampling. Data were collected through questionnaires and analyzed using path analysis and the Sobel test. The results show that organizational justice and organizational support have a positive and significant effect on work motivation. Organizational justice and organizational support also have a positive and significant effect on work engagement. Furthermore, work engagement has a positive and significant effect on work motivation and significantly mediates the relationship between organizational justice and organizational support on work motivation. These findings indicate that fair organizational practices and institutional support can strengthen employee motivation, particularly when employees are psychologically engaged in their work. The study contributes to human resource management literature by emphasizing the mediating role of work engagement in explaining how organizational factors influence employee motivation in higher education institutions.